2019
DOI: 10.1038/s41598-019-56320-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the hepatoprotective effect of developed lipid-polymer hybrid nanoparticles (LPHNPs) encapsulating naturally extracted β-Sitosterol against CCl4 induced hepatotoxicity in rats

Abstract: The hepatoprotective effect of β-Sitosterol (BSS), a natural phytosterol, after being formulated into a suitable pharmaceutical drug delivery system has not been widely explored. BSS was isolated from Centaurea pumilio L., identified and formulated as lipid-polymer hybrid nanoparticles (LPHNPs) using the poly(D,L-lactide-co-glycolide) polymer and DSPE-PEG-2000 lipid in different ratios. The selected formulation, prepared with a lipid: polymer: drug ratio of 2:2:2, had an entrapment efficiency (EE%) of 94.42 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 72 publications
0
26
0
Order By: Relevance
“…The animal models exposed to CCl 4 and D-gal/LPS have been extensively applied for investigating the underlying mechanisms of acute liver injury. CCl 4 is a widely used chemical toxicant and causes severe liver tissue damage by the cytochrome P450 enzymes to form reactive intermediates, such as trichloromethylfree radicals and peroxyl radical, which results in lipid peroxidation and hepatocyte necrosis [24][25][26]. Lipopolysaccharide (LPS), also known as endotoxin, is a major component of the outer membrane of Gramnegative bacteria, which induces a strong inflammatory response [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The animal models exposed to CCl 4 and D-gal/LPS have been extensively applied for investigating the underlying mechanisms of acute liver injury. CCl 4 is a widely used chemical toxicant and causes severe liver tissue damage by the cytochrome P450 enzymes to form reactive intermediates, such as trichloromethylfree radicals and peroxyl radical, which results in lipid peroxidation and hepatocyte necrosis [24][25][26]. Lipopolysaccharide (LPS), also known as endotoxin, is a major component of the outer membrane of Gramnegative bacteria, which induces a strong inflammatory response [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, integrated miRNAomics, proteomics and metabolomics analysis found that geniposide could upregulate the protein levels of isocitrate dehydrogenase (IDH) 1 and 2 through downregulating the expression of miR-144-5p and then modulate energy metabolism in ethanol-induced apoptosis hepatocyte model in vitro ( Qiu et al, 2017 ). Lipid peroxidation induced by CCl 4 treatment can alter the permeability of the cell membrane, resulting in damage to the intracellular organelle membrane structures, such as mitochondria, endoplasmic reticulum, and Golgi apparatus, etc., which further triggers the metabolic disorders in hepatocytes ( Abdou et al, 2019 ). Untargeted metabolomics were used to analyze the metabolic regulatory effects of geniposide on CCl 4 -induced liver fibrosis model.…”
Section: Discussionmentioning
confidence: 99%
“…For β-sitosterol, it is a regarded as a safe nutritional supplement that can be sold commercially in the market [ 22 ]. It was recognized to possess several bioactivities including anti-nociceptive [ 23 ], anxiolytic & sedative effects [ 24 ], analgesic [ 25 ], immune modulatory [ 26 ], antimicrobial [ 27 ], anti-inflammatory [ 28 ], protective effect against non-alcoholic fatty liver disease [ 29 ], lipid lowering [ 30 ], hepatoprotective [ 31 ], protective effect on respiratory diseases [ 32 ], wound healing [ 33 ], antidiabetic [ 34 ], antioxidant [ 35 ], and anticancer [ 36 ]. As an anticancer, it could inhibit the growth of HeLa, HT-29, KB, and MCF-7 cell lines with moderate IC 50 values ranging from 0.099 to 1.49 μg/mL [ 3 ].…”
Section: Discussionmentioning
confidence: 99%